A nostalgic Peranakan journey in Melaka: Duo-ethnographic conversations between a Nyonya and Baba. (October 2019) - Tan, Eunice; Teoh, Simon
Abstract: A UNESCO World Heritage Listed historic city, Melaka embodies a vibrant multi-ethnic Asian heritage, straits-colonial legacy and cultural landscape that has been attracting tourists from within Asia and the wider world. In particular, Melaka is renowned for its rich Peranakan (Straits Chinese) cultural heritage and history. This work presents the divergent narratives of two Peranakan Chinese on a nostalgic, ancestral tourism journey in Melaka. Specifically, it explores the dimensions of nostalgia, authenticity and diaspora in cultural heritage tourism, framed within the affecting gaze of cultural, diasporic and reminiscent lenses through which we consume tourism experiences. Through our tourism lived experience and duo-ethnographic conversations, we explore our shared Southeast Asian ancestry, reflect on past traditions and question representations of our Peranakan Chinese heritage within four main themes: (1) reflective nostalgia, (2) the imagined past, (3) objective authenticity, and (4) existential authenticity. Highlights: We reminisce and construct meanings through nostalgia, authenticity and diaspora. Our Gaze Prism is influenced by our cultural, diasporic and reminiscent lenses. Duo-ethnography offers a polyvocality of insights on authenticity and nostalgia. Meaningful we-relationships connect people and places, temporally and spatially.